2009
DOI: 10.3917/ecoi.118.0101
|View full text |Cite
|
Sign up to set email alerts
|

Vietnam's export-led growth model and competition with China

Abstract: Résumé L’émergence de la Chine a suscité des interrogations quant à la possibilité pour de nouveaux pays asiatiques de décoller et de rejoindre le groupe des économies émergentes. Cet article s’intéresse à cette question dans le cas du Vietnam qui, au cours de ces vingt dernières années, a suivi de près le chemin emprunté par la Chine, avec beaucoup de succès. Il décrit d’abord la stratégie vietnamienne de croissance tirée par l’exportation, et ses résultats en termes de PIB et d’intégration à l’économie mondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Despite their potentially ambiguous impacts, FTAs and inward FDI are considered to be key drivers of Vietnam's trade. Since Vietnam's "Doi Moi" or renovation policy 1 was launched in the mid-1980s to facilitate change from a centrally planned to a market-oriented economy, Vietnamese trade policy has been based on pursuing an export-led growth strategy (Nguyen and Xing, 2008), in which trade liberalisation, exports and FDI have been promoted (Chaponnière and Cling, 2009). Therefore, examining the effects of both trade liberalisation and FDI on Vietnam's trade is important, especially when foreign trade has become a primary factor driving economic growth (Kastelle and Liesch, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their potentially ambiguous impacts, FTAs and inward FDI are considered to be key drivers of Vietnam's trade. Since Vietnam's "Doi Moi" or renovation policy 1 was launched in the mid-1980s to facilitate change from a centrally planned to a market-oriented economy, Vietnamese trade policy has been based on pursuing an export-led growth strategy (Nguyen and Xing, 2008), in which trade liberalisation, exports and FDI have been promoted (Chaponnière and Cling, 2009). Therefore, examining the effects of both trade liberalisation and FDI on Vietnam's trade is important, especially when foreign trade has become a primary factor driving economic growth (Kastelle and Liesch, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In Vietnam, although the ELG theory has been applied for more than 30 years, there are few studies on the relationship between exports and economic growth. The reasonableness of Vietnam's ELG strategy in relation to economic growth as well as the dependence of Vietnamese exports on the US and Chinese markets were described by Chaponnière & Cling [37]. This relationship was verified in a study conducted by Cong [38], who tested the impact of exports on economic growth by using the causality test model of Granger [9], Balassa [39], and Feder [11] and found that exports not only play an important role in promoting the country's economic growth but also actively contribute to the development of non-export.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Vietnam had stressed on being the export-led growth country since the reformation in the mid-1980s (Chaponnière and Cling, 2009). Since 2012, Vietnam is experiencing a trade surplus as the export growth had increased more than the import (Clarke et.al, 2017…”
Section: Current Scenario Of the Export Industry Of Vietnammentioning
confidence: 99%